The Influence of Self–Efficacy and Employee Empowerment on Organizational Citizenship Behavior through Job Satisfaction - Hermawati, Rahmi; Moeins, Anoesyirwan; Suhardi, Eka (Journal of World Science, 2023)
The purpose of this research is to form the minds of employees who have low self-efficacy so that they are more productive at work according to gender, age and workload. It also aims to identify and analyze the effect of self-efficacy and employee empowerment on civic organizational behaviour through job satisfaction. Research methodology with a qualitative type of library research. The results of the study are based on the results of the literature review analysis, including indicators of low self-efficacy, which are influenced by the failure to achieve employee welfare and no reward. A work system that is not conducive can influence employee loyalty and dedication to increase awareness at work, motivation, sense of responsibility, and quality in completing each work carried out within a predetermined time limit. Working professionally and loyally is a characteristic of employees who take their work seriously. High seriousness values for employees with maximum work performance can reduce the low self-efficacy of employees. Increasing self-efficacy and empowering employees can improve civic behaviour in organizations. Self-efficacy and employee empowerment help increase employees' self-confidence and abilities in carrying out their duties so that they can more effectively and efficiently contribute to the organization.